A new propeller flap based upon medial-plantar-artery perforator for reconstruction of the distal weight-bearing foot. (June 2015) - Coriddi, M.; Carraher, A.M.; Agnese, D.; Chandawarkar, R.Y.
Abstract: Reconstruction of the weight-bearing areas of the plantar foot is challenging with limited options. Here, we describe a medial-plantar-artery perforator-based propeller flap for the reconstruction of a distal plantar defect. Flap design and advantages of this flap are discussed.